‘GETTING HERE FROM THERE’: TRAUMA AND TRANSFORMATION IN CANADIAN MILITARY EDUCATION - Ronald G. Haycock (Scientia Militaria, 2012)
In early 1997, the Canadian Minister of National Defence publicly issued an excoriating report that roundly condemned the poor state of leadership, ethics discipline, professional knowledge and education in the Canadian Armed Forces particularly among officers. His public exposure stemmed from a series of traumatic events that occurred in the four previous years. The most damning one had been the appalling revelation that some soldiers of the Canadian Airborne Regiment, then on a peacekeeping mission in Somalia, had beaten to death a young Somali teenager. The trail led right back to senior officers in Canada and there was evidence of a cover-up. The embarrassed government was forced into appointing a top level Somalia Commission of Inquiry1. Then, in the next several months, followed revelations recorded on camera of grotesque initiation rites and racism in airborne units and others. The usually complacent and unmilitary Canadian public was shocked and indignant.2 The government promptly disbanded the Canadian Airborne Regiment. How, many asked, did the Canadian Forces get here from its excellent performance in past decades? It had fought well in both World Wars, in Korea and had served with great distinction in the many United Nations missions since that time. Canadians, after all prided themselves believing that their forces were the humanitarian ‘honest northern brokers’ and perhaps the world’s best peacekeepers.